Welfare State and Life Satisfaction: Evidence from Public Health Care - Jani-Petri Laamanen; Kaisa Kotakorpi (Tinbergen Institute, 2007)
We examine the effect of publicly provided health care on welfare by combining local level data on public health care, and individual level data on life satisfaction. It is shown that relatively high expenditures in health care have a positive effect on individuals' life satisfaction in our data. We further illustrate how life satisfaction data can be used to directly test theoretical hypotheses about how the welfare effect of public provision should vary among different groups in the population. We find some evidence for an ends-against-the-middle equilibrium (Epple and Romano, 1996) in the provision of public health care, where middle-income individuals prefer higher public expenditure at the margin than low-income or high-income individuals. Further, our results indicate that valuation for health care depends on individual political orientation.
Keywords: H44; I18; 330; Life satisfaction; public provision; health care; Zufriedenheit; Gesundheitsversorgung; Gesetzliche Krankenversicherung; Wohlfahrtsanalyse; Sozialstaat; Welt